2016
DOI: 10.1177/0963662516661090
|View full text |Cite
|
Sign up to set email alerts
|

Opposing ends of the spectrum: Exploring trust in scientific and religious authorities

Abstract: Given the ethical questions that surround emerging science, this study is interested in studying public trust in scientific and religious authorities for information about the risks and benefits of science. Using data from a nationally representative survey of American adults, we employ regression analysis to better understand the relationships between several variables-including values, knowledge, and media attention-and trust in religious organizations and scientific institutions. We found that Evangelical C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 48 publications
(70 reference statements)
6
34
0
5
Order By: Relevance
“…To this extent, our findings parallel those found in the research on motivated reasoning and cultural cognition (e.g., Nisbet and Goidel 2007;Kahan et al 2010;Druckman and Bolsen 2011) that have consistently found that preexisting values and perceptions bias and filter the perception of available factual information. These findings also echo the work of other recent research that speaks to growing lack of public trust in science (Achterberg et al 2017;Cacciatore et al 2016), which, in our estimation, could function as one such bias. If the public holds views that scientists have ulterior motives that compromise the veracity of their claims, other rationales, such as ideological orientation, may be more likely to guide behavior.…”
Section: Implications For Science Communicationsupporting
confidence: 91%
“…To this extent, our findings parallel those found in the research on motivated reasoning and cultural cognition (e.g., Nisbet and Goidel 2007;Kahan et al 2010;Druckman and Bolsen 2011) that have consistently found that preexisting values and perceptions bias and filter the perception of available factual information. These findings also echo the work of other recent research that speaks to growing lack of public trust in science (Achterberg et al 2017;Cacciatore et al 2016), which, in our estimation, could function as one such bias. If the public holds views that scientists have ulterior motives that compromise the veracity of their claims, other rationales, such as ideological orientation, may be more likely to guide behavior.…”
Section: Implications For Science Communicationsupporting
confidence: 91%
“…Previous research has performed a comparative analysis of the credibility of different social institutions (including religious authorities) regarding scientific issues such as climate change, and the way in which confidence in scientific institutions and scientists is associated with trust in other sources (e.g. Cacciatore et al, 2018;Carlisle et al, 2010;Liu and Priest, 2009;Myers et al, 2017;Peters et al, 1997;Priest et al, 2003). This study advances further, in line with the approach of Carlisle et al (2010), and while maintaining constant the scientific results attributed to scientists, an attempt is made to ascertain whether different sources of the same information affect its credibility.…”
Section: Introductionmentioning
confidence: 99%
“…Second, since previous studies have established that religious leaders have a strong in uence on their followers (Cacciatore et al 2018;McPhetres and Zuckerman 2018;Scheufele et al 2009), we strongly propose that as scientists scramble for the development of a COVID-19 vaccine, they also establish a strong partnership with religious institutions through their leaders. This working relationship should be rooted in transparency of the ongoing vaccine development processes.…”
Section: Discussionmentioning
confidence: 92%
“…While religion assists in coping with life stressors, studies have also demonstrated religiosity to be strongly and positively correlated with trust in informal sources of information such as religious organization's website, spiritual leaders, and family/friends (Cacciatore et al 2018;Scheitle et al 2018).…”
Section: Religious Coping During Stressful Eventsmentioning
confidence: 99%
See 1 more Smart Citation